REDUCING ION Pb CONCETRATION IN ELECTROPLATING WASTE WATER WITH BIOSORPTION PROCESS AND STIRRING - Nana Dyah S., Erwan Adi S., (Jurnal Teknik Kimia, 2010)
This research aim to know the influence of stirring process to the capability of Phanaerochaete chrysosporiumto absorb heavy metal ions of Pb (II) in electroplating waste water. The methods of this researchstarting by developing and treatment of Phanaerochaete chrysosporium and then this biomass wascontacted with waste water that contain of Pb (II)in the stirring variable is 50, 100, 150, 200, 250 rpm andin the biomass consentration is 1,2 and 3 (mg/lt). After contacted 150 minute the result has analyzed byAAS. From the analyzed the metal ion of Pb(II) was known and then the analysis of data was done bycomparing the process before contacted and after contacted. From this research get that the optimimprocess is in 200 rpm, the number of adsorption metal ion of Pb(II) was increasing until 200 rpm, and inthis condition the optimum adsorption reach 66,79%.Keyword : Biosorption, stirring, waste water electroplating.